When Father Doesn't Know Best: Selective Disagreement Between Self‐Report and Informant Report of the Broad Autism Phenotype in Parents of a Child with Autism. Issue 6 (22nd October 2014) - Sasson, Noah J.; Faso, Daniel J.; Parlier, Morgan; Daniels, Julie L.; Piven, Joseph
<x xml:space="preserve">Abstract</x> The Broad Autism Phenotype Questionnaire (BAPQ) is a reliable tool for identifying three autism‐related traits—social aloofness, pragmatic language abnormalities and rigid personality—within families of a person with autism and the general population. Although little is known concerning agreement between self‐report and informant report versions of the BAPQ, identifying individual characteristics affecting agreement between the two can highlight important considerations for maximizing its yield, particularly when only one version is administered. Here, analysis of self‐report and informant report of the BAPQ completed by 444 parents of a child with autism revealed moderate to strong agreement between the two versions for all three broad autism phenotype (BAP) traits when the self‐reporting parent did not possess the trait being assessed. In contrast, disagreement selectively occurred when the assessed parent was positive for the BAP trait being rated. This pattern was driven primarily by fathers who were positive for a BAP trait endorsing lower levels of that trait relative to informant report. This discrepancy did not occur for mothers, nor did it occur for fathers lacking BAP traits. Because this pattern was specific to fathers positive for BAP traits, it likely reflects selective "blind spots" in their self‐reporting and not poorer self‐reporting by fathers more broadly, nor a general tendency of overreporting by informant mothers. The presence of BAP traits in informing parents, however, largely did not reduce agreement between self‐report and informant report. In sum, self‐report may underestimate the presence of BAP traits in fathers but is generally consistent with informant report for mothers. Autism Res2014, 7: 731–739. © 2014 International Society for Autism Research, Wiley Periodicals, Inc.